Disruptive Technologies and Peer-learning for Dialogue and Reflection - Jespersen, Ariana; Kjærgaard, Thomas; Yagelski, Robert (Proceedings for the European Conference on Reflective Practice-based Learning 2025, 2025)
This paper presents a study of reflection in online, intercultural dialogues between teacher students from The United States of America and Denmark. The study is based on a Collaborative Online International Learning (COIL) exchange between the teacher education programs at University at Albany, SUNY, USA, and University College of Northern Denmark, Aalborg. The COIL project aimed to provide students with cross-cultural perspectives on teaching while fostering reflection about how cultural factors shape educational systems and practice. COIL allows for increased opportunity for the intercultural exchange of ideas without the difficulties of traditional physical exchange. However, it can also potentially decrease experiences of “human” interaction and reflection. Thus, this study explores how online exchange can be structured to create optimal opportunities for peer-learning and reflection. The study’s data is produced through a mixed survey, excerpts from student reflections, comments on the online platform Microsoft Teams, and student interviews. The interviews and the specific student’s reflection assignments formulate three cases that illustrate different approaches to participation in online dialogue and subsequent routes to reflection. The methods of case study and informed grounded theory investigate how the differences between asynchronous and synchronous multimodal exchange impact the students’ experiences of the selected affordances of an online platform as disruptive or non-disruptive, and how this influences their intercultural dialogue and level of reflection. The conclusions from the analysis suggest recommendations for additional scaffolding of online exchanges in future practice as well as themes for further research.